2006
DOI: 10.1002/bem.20286
|View full text |Cite
|
Sign up to set email alerts
|

Role of blood flow on RF exposure induced skin temperature elevations in rabbit ears

Abstract: In this in vivo study, we measured local temperature changes in rabbit pinnae, which were evoked by radiofrequency (RF) exposure for 20 min at localized SAR levels of 0 (sham exposure), 2.3, 10.0, and 34.3 W/kg over 1.0 g rabbit ear tissue. The effects of RF exposures on skin temperature were measured under normal blood flow and without blood flow in the ear. The results showed: (1) physiological blood flow clearly modified RF induced thermal elevation in the pinna as blood flow significantly suppressed temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Heat generation in exposed tissue [Jia et al, ] and organs [Kojima et al, ] was observed following the exposure to a high‐intensity RF signal, which may affect physiological functions in animals. Indeed, whole‐body [Jauchem and Frei, ] and local [Masuda et al, ] exposure to a high‐intensity RF signal reportedly increased the body temperature in animals.…”
Section: Introductionmentioning
confidence: 99%
“…Heat generation in exposed tissue [Jia et al, ] and organs [Kojima et al, ] was observed following the exposure to a high‐intensity RF signal, which may affect physiological functions in animals. Indeed, whole‐body [Jauchem and Frei, ] and local [Masuda et al, ] exposure to a high‐intensity RF signal reportedly increased the body temperature in animals.…”
Section: Introductionmentioning
confidence: 99%
“…High-intensity exposure to radiofrequency electromagnetic fields (RF) generates heat in exposed tissue (3,15) and organs (17,43). Thus this type of exposure has the capacity to affect physiological functions in mammals via heat generation.…”
mentioning
confidence: 99%